Impact of elosulfase alfa in patients with morquio A syndrome who have limited ambulation: An open‐label, phase 2 study. Issue 2 (24th October 2016) - Harmatz, Paul R.; Mengel, Eugen; Geberhiwot, Tarekegn; Muschol, Nicole; Hendriksz, Christian J.; Burton, Barbara K.; Jameson, Elisabeth; Berger, Kenneth I.; Jester, Andrea; Treadwell, Marsha; Sisic, Zlatko; Decker, Celeste
Abstract : Efficacy and safety of elosulfase alfa enzyme replacement therapy (ERT) were assessed in an open‐label, phase 2, multi‐national study in Morquio A patients aged ≥5 years unable to walk ≥30 meters in the 6‐min walk test. Patients received elosulfase alfa 2.0 mg/kg/week intravenously for 48 weeks. Efficacy measures were functional dexterity, pinch/grip strength, mobility in a modified timed 25‐foot walk, pain, quality of life, respiratory function, and urine keratan sulfate (KS). Safety/tolerability was also assessed. Fifteen patients received elosulfase alfa, three patients discontinued ERT due to adverse events (two were grade 3 drug‐related adverse events, the other was not drug‐related), and two patients missed >20% of planned infusions; 10 completed treatment through 48 weeks and received ≥80% of planned infusions (Modified Per Protocol [MPP] population). The study population had more advanced disease than that enrolled in other trials. From baseline to week 48, MPP data showed biochemical efficacy (urine KS decreased 52.4%). The remaining efficacy results were highly variable due to challenges in test execution because of severe skeletal and joint abnormalities, small sample sizes, and clinical heterogeneity among patients. Eight patients showed improvements in one or more outcome measures; several patients indicated improvements not captured by the study assessments (e.g., increased energy, functional ability). The nature of adverse events was similar to other elosulfase alfa studies. This study illustrates the considerable challenges in objectively measuring impact of ERT in very disabled Morquio A patients and highlights the need to examine results on an individual basis. © 2016 The Authors. American Journal of Medical Genetics Part A Published by Wiley Periodicals, Inc.